A docência na educação de jovens e adultos: um estudo a partir do Programa Mulheres Mil no IFSUL – Câmpus Sapiranga/RS - Heckler, Gisele Lopes (Universidade do Vale do Rio dos Sinos, 2017)
This thesis aims to analyze teaching in Youth and Adult Education based on the Women Thousand Program, offered by IFSUL / RS - Campus Sapiranga, RS, Brazil, in the second half of 2014. These women, as participants in the program, were apart from school and have varying professional backgrounds. In order to carry out the study, theoretical references on teaching in the EJA were used: professional education, popular education, public education policies and gender issues. The theoretical foundation is based on related themes, especially teaching in Youth and Adult Education, the contributions of Popular Education, to Professional Education, the issues of Gender. Methodology used has affinities with the participant research. The data were collected through semi-structured interviews with the program coordinator and she graduates, and discussion groups with she graduates and teachers. They were analyzed from the contributions of the documentary method and the formation-research. The research allowed to identify that the participating teachers reflect on their practice. Through their understanding of teaching, teachers seek to practice a practice that focuses, firstly, on the specific characteristics of the PMM public, providing the most adequate conditions for learning, without losing sight of the expectations of the she students and their context, seeking postures and methodologies that meet the objectives of the program, specially to raise the self-esteem of these women and promote their learning and permanence in the courses. The study seeks to contribute with the proposal that assists in the training and teaching practice for this specific public, to think about an initial and / or continuous formation that meets the demands of those who wish or need to teach in the EJA and in the education of women, conceived in the specificities of these students and their real needs, could they be the emancipation and empowerment to achieve a necessary transformation from the prevailing social order to a much more egalitarian one.
Keywords: Docência; Educação de jovens e adultos; Educação profissional; Mulheres mil e gênero; Teaching; Youth and adult education; Professional education; Women thousand and gender; ACCNPQ::Ciências Humanas::Educação